Diana, princess of the people - Stone, Tanya Lee. (Brookfield, Conn. : Millbrook Press, 1999)
Follows the life of Diana, Princess of Wales, from her childhood, through her experiences with the royal family and public life, to her death in 1997.
Includes bibliographical references (p. 44-45) and index.
Keywords: Diana, -- Princess of Wales, -- 1961-1997 -- Juvenile literature; Princesses -- Great Britain -- Biography -- Juvenile literature; Princesses -- Juvenile literature; Women -- Biography -- Juvenile literature